PowerShell for SharePoint 2013 : how-to - Mann, Steve, 1950- (How-to, 2013)
Need fast, reliable, easy-to-implement solutions for automating SharePoint 2013 administration with PowerShell? This guide delivers exactly what you're looking for: step-by-step help and guidance with the tasks you'll perform most often. You'll find tested PowerShell scripts and techniques for managing installations, servers, farms, IIS, users, services, sites, data, solutions, enterprise services, search, PerformancePoint business intelligence, and more. This edition adds time-saving techniques for managing user licensing and new SharePoint 2013 service applications, covers new cmdlets, and contains two new reference appendices. This focused resource for scripting SharePoint with PowerShell provides all the answers you need - now! Fast, Accurate, and Easy to Use! Run PowerShell scripts from the SharePoint 2013 Management Shell console Perform unattended SharePoint installations Configure new farms, add servers, and manage sites Create new site collections and sub-sites Review and set Farm Configuration Values and SharePoint Designer Settings Display, get, create, remove, configure, and extend web applications Create, manage, remove, back up, and restore SharePoint databases Work with SharePoint solutions and features Automatically publish and manage content Establish and change external data connections via Business Data Connectivity Service Control the new versions of Excel, Access, Visio, and Word Services Script Office Web Apps to deliver more robust web/mobile solutions Manage PerformancePoint business intelligence via cmdlets Administer Enterprise Search, InfoPath Form Services, profiles, metadata, and Secure Store Streamline Work Management Services to help users track tasks more efficiently.